The Effect of Certification Allowances and Motivation on Teacher’s Performance in Improving Education Quality - Yuslinar, Yuslinar; Harapan, Edi; Wahidy, Achmad (Yayasan Sembilan Pemuda Indonesia, 2023)
This study examines the extent to which certification allowances and motivation affect teacher’s performance in improving the quality of public elementary school education in Pemulutan Induk District. This is a quantitative with descriptive approach. The sample in this study was 87 respondents. The questionnaire is provided in the form of a URL https://forms.gle/dhHt23H7tgmPmKX56 as instrument, then analyzed descriptively using the SPSS version 25. The findings of this study show that certification allowances and motivation affect teacher’s performance in improving the quality education partially and simultaneously. It gives new insight to improve education quality, the principals and all stakeholders should give attention to the certification allowances, and teacher’s motivation, and it will improve the teacher’s performance.